Intrahepatic intestinal loop through a congenital mesenteric hernia - Przemyslaw Galazka; Natalia Sadej; Marika Reszczynska-Domagala; Krzysztof Dymek; Kacper Kroczek; Irena Daniluk-Matras (Elsevier, 2017)
Congenital internal mesenteric hernia is a rare cause of intestinal obstruction in the newborn. We report on a new unusual feature of combined internal transmesenteric hernia with intrahepatic location of the intestinal loop. We present also our controversial therapeutic approach based on the intention to finally resolve the problem of internal hernia in the newborn.